Intragenerational social mobility and functional somatic symptoms in a northern Swedish context: analyses of diagonal reference models. Issue 1 (December 2017) - Jonsson, Frida; Sebastian, Miguel; Hammarström, Anne; Gustafsson, Per
Abstract Background Research indicate that social class mobility could be potentially important for health, but whether this is due to the movement itself or a result of people having been integrated in different class contexts is, to date, difficult to infer. In addition, although several theories suggest that transitions between classes in the social hierarchy can be stressful experiences, few studies have empirically examined whether such movements may have health effects, over and above the implications of "being" in these classes. In an attempt to investigate whether intragenerational social mobility is associated with functional somatic symptoms in mid-adulthood, the current study tests three partially contrasting theories. Method Thedissociative theory suggests that mobility in general and upward mobility in particular may be linked to psychological distress, while thefalling from grace theory indicates that downward mobility is especially stressful. In contrast, theacculturation theory holds that the health implications of social mobility is not due to the movement itself but attributed to the class contexts in which people find themselves. Diagonal Reference Models were used on a sample of 924 individuals who in 1981 graduated from 9th grade in the municipality of Luleå, Sweden. Social mobility was operationalized as change in occupational class between age 30 and 42 (measured in 1995 and 2007). The health outcome was functional somatic symptoms at age 42, defined as a clustering self-reported physical symptoms, palpitation and sleeping difficulties during the last 12 months. Results Overall mobility was not associated with higher levels of functional somatic symptoms compared to being immobile (p  = 0.653). After controlling for prior and current class, sex, parental social position, general health, civil status, education and unemployment, the association between downward mobility was borderline significant (p  = 0.055) while upward mobility was associated with lower levels of functional somatic symptoms (p  = 0.03). Conclusion The current study did not find unanimous support for any of the theories. Nevertheless, it sheds light on the possibility that upward mobility may be beneficial to reduce stress-related health problems in mid-life over and above the exposure to prior and current class, while downward mobility can be of less importance for middle-age health complaints.